Gothic Elements in Jane Eyre by Charlotte Brontë and Wuthering Heights by Emily Brontë - Lulová, Martina (Univerzita Pardubice, 2014)
The aim of this paper is to describe the essential characteristic features of the nineteenth-century Female Gothic novel and to analyse them in the Victorian novels written by the Brontë sisters, Charlotte Brontë´s Jane Eyre and Emily Brontë´s Wuthering Heights. Firstly, the paper deals with the literary as well as historical context of the Female Gothic tradition. Secondly, the typical motifs and literary devices of the nineteenth-century Female Gothic are described and subsequently analysed in the novels. The novels are briefly compared in terms of the presence of the features in them.
Gotické elementy v románech Jane Eyre a Wuthering Heights
Keywords: ženská gotika; Na větrné hůrce; Jana Eyrová; hrdinky; společenské postavení žen; rozdvojená osobnost; uncanny; Female Gothic; Wuthering Heights; Jane Eyre; heroines; social position of women; split personality; uncanny